Biologi Ikan Uceng (Nemachilus fasciatus C.V.) di Sungai Banjaran Kabupaten Banyumas - Slamet Risyanto; Erwin Riyanto Ardli; Isdy Sulistiyo (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2012)
A research on fish biology Nemachilus fasciatus CV was conducted in River Banjaran Banyumas. The purpose of this study was to assess the biological aspects, including the nature of growth, Gonado somatic index, fecundity, sex ratio and natural food habits. The method used is survey, the technique used was stratified random sampling.  Banjaran river was divided into nine stations: three stations on the upstream side of the river, three stations in the middle of the river and three stations on the river downstream. The results showed the data aspects of the biology of N. fasciatus in rivers Banjaran was allometrik growth, the gonado somatic index ranged from 5.40 to 17.46%. The highest fecundity of 7,567 items found in fish N. fasciatus which has a total length of 74 mm and 3.25 g body weight. Fecundity was as low as 1,665 points with fish body length of 58 mm and 2.02 g body weight.  The sex ratio is 1:1,25.  The natural food with the highest frequency of occurrence was on Pediastrum and low frequency of occurrence is in Cosmarium and Bronchionus.